Karakterisasi Bakteri Asam Laktat Proteolitik pada Bekasam - Wikandari, Prima Retno; Suparmo, Suparmo; Marsono, Yustinus; Rahayu, Endang Sutriswati (Jurnal Natur Indonesia, 2012)
Bekasam is a traditional fermented fish from Indonesia. It is made from fish  in which  the gills and  gut  had been  discarded,  washed,  and  mixed with salt, after two days, it was covered  with  rice  and  salt,  and then  fermented  for  5-7 days  at room  temperature.  Bekasam  is perceived to have antihypertensive activity, which is though to be the activity of bioactive peptides, the product of protein degradation  during  the bekasam fermentation. The research was aim to isolate the indigenous lactic  acid  bacteria  that  produce strong  proteolytic  capabilities.  The lactic  acid bacteria were collected from 3  kinds of bekasam (tilapia, milkfish, and tuna bekasam). Isolation  of the lactic acid bacteria was done         on agar medium containing MRS + CaCO3, and  the screening of the proteolytic bacteria  was done by growing the isolated  culture on  skim agar.   The colonies  that produce clear zone  were identified  as proteolytic  lactic acid  bacteria. Some of 180  isolated strains of acid  producing bacteria   that produce clear zone on MRS agar were found 150 strains of  lactic acid  bacteria, and  84  strains  showed  their  proteolytic activity.  The later  were identified morphologically and biochemical as Lactobacillus, Pediococcus and Leuconostoc genera.  Selection  was further conducted based on the height of the proteolytic and homofermentative fermentation activities. Upon species identification using API CH 50 kit,  the  selected strains belong to species of Lactobacillus plantarum, Lactobacillus pentosus, and Pediococcus pentosaseus.